Peningkatan Kualitas Proses dan Hasil Belajar Biologi dengan Experiental Learning Siswa Kelas X MIPA 7 SMA Negeri 1 Makassar - Hajar, Abdul (Biology Teaching and Learning, 2019)
Abstract.Achieving effective teaching and learning is not possible only with methods that are teacher centered or one-way communication, but must also be a method that is multi-purpose or student centered. The study aims to determine the improvement of the quality of the process and student learning outcomes with experiential learning on biology subjects. Research is a class action research, as an alternative effort that can be done by teachers to develop and improve the quality of learning, where classroom teachers are actors of action or teachers as researchers. This research is a cyclical study consisting of 4 stages, namely: planning, taking action, observing and reflecting. This research was conducted in class X MIPA 7 in Makassar 1 Public High School, with 34 subjects as subjects, in the even semester 2018/2019 academic year. The results showed that the process and results of learning biology can be improved by using experiential learning in class X MIPA 7 Makassar 1 Public High School. Keywords: learning processes and results and experiential learning